Io e l'altro (Io) tra bilinguismo, biculturalismo e identità culturale del Sé "rappato" di seconda generazione (Altre Modernità, 2020)
This work aims to analyze the continuously increasing rap songs of second-generation immigrants, from a multidisciplinary perspective and on an exclusively synchronic level. The second generation rappers are children of immigrants or mixed couples, born and raised in Italy, who use the language of rap as a means of constructing their own identity. Suspended "between two cultures" (Baumann 1), or between two worlds, the singers create in their songs a "third space" (Bhabha 54-56) steeped in contaminations and creolizations. Furthermore, the simultaneous use of two or more codes makes coexist in their lyrics a plurality of languages that has now become a "new plurality" (Ferrari 157). It does not reflect a specific belonging to a place or culture, but the desire to situate oneself between two places. Since this is a in continuously expanding phenomenon, the examples are numerous. For the purpose of this paper we analysed a selection of songs of five of the second-generation rappers that are much followed at a social network level. We then conducted a linguistic analysis aimed at investigating on the peculiar presence in the lyrics of both Italian and "immigrant languages" (Vedovelli 97). The cross-linguistc influence phenomena (code-switching and code-mixing) together with the choice of lexemes with a strong emotional connotation act as identity representation tools. The identity is always based on duality and on the conflict that arises from the continuous relating of the Self with the Other and from the exchange between the Self and the Other, in which the otherness refers to both the others and the other part of the Self.